Overcoming substrate limitations for improved production of ethylene in E. coli. Issue 1 (December 2016) - Lynch, Sean; Eckert, Carrie; Yu, Jianping; Gill, Ryan; Maness, Pin-Ching
Abstract Background Ethylene is an important industrial compound for the production of a wide variety of plastics and chemicals. At present, ethylene production involves steam cracking of a fossil-based feedstock, representing the highest CO2 -emitting process in the chemical industry. Biological ethylene production can be achieved via expression of a single protein, the ethylene-forming enzyme (EFE), found in some bacteria and fungi; it has the potential to provide a sustainable alternative to steam cracking, provided that significant increases in productivity can be achieved. A key barrier is determining factors that influence the availability of substrates for the EFE reaction in potential microbial hosts. In the presence of O2, EFE catalyzes ethylene formation from the substrates α-ketoglutarate (AKG) and arginine. The concentrations of AKG, a key TCA cycle intermediate, and arginine are tightly controlled by an intricate regulatory system that coordinates carbon and nitrogen metabolism. Therefore, reliably predicting which genetic changes will ultimately lead to increased AKG and arginine availability is challenging. Results We systematically explored the effects of media composition (rich versus defined), gene copy number, and the addition of exogenous substrates and other metabolites on the formation of ethylene inEscherichia coli expressing EFE. Guided by these results, we tested a number of genetic modifications predicted to improve substrate supply and ethylene production, including knockout of competing pathways and overexpression of key enzymes. Several such modifications led to higher AKG levels and higher ethylene productivity, with the best performing strain more than doubling ethylene productivity (from 81 ± 3 to 188 ± 13 nmol/OD600 /mL). Conclusions Both EFE activity and substrate supply can be limiting factors in ethylene production. Targeted modifications in central carbon metabolism, such as overexpression of isocitrate dehydrogenase, and deletion of glutamate synthase or the transcription regulator ArgR, can effectively enhance substrate supply and ethylene productivity. These results not only provide insight into the intricate regulatory network of the TCA cycle, but also guide future pathway and genome-scale engineering efforts to further boost ethylene productivity.